2021
DOI: 10.2991/aer.k.211222.033
|View full text |Cite
|
Sign up to set email alerts
|

Smart Trash Can: Innovation of Automatic Trash Can with Arduino Uno-Based as an Effort to Support Global Sustainable Development Goals (SDGs) Action

Abstract: Garbage is an item that we encounter every day and often causes problems. Based on statistical data from the 2020 National Waste Management Information System, in the City of Yogyakarta the highest percentage of waste by type is organic waste consisting of food waste with a percentage of 50.21%. One of the problems that must be addressed is the presence of waste mixed with other types of waste, this is due to the lack of public awareness and knowledge in sorting waste. Therefore, appropriate treatment is neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
0
0
1
Order By: Relevance
“…Penelitian tentang pembuatan tempat sampah cerdas pernah dilakukan oleh [7] menggunakan arduino uno, sensor ultrasonik dan servo. Penelitian lain dilakukan juga oleh [8] dengan arduino uno yang dibuat untuk sampah organik, anorganik dan sampah metal dalam mendukung Sustainable Development Goals (SDGs). Namun dua penelitian ini belum dilengkapi dengan sistem monitoring.…”
Section: Pendahuluanunclassified
“…Penelitian tentang pembuatan tempat sampah cerdas pernah dilakukan oleh [7] menggunakan arduino uno, sensor ultrasonik dan servo. Penelitian lain dilakukan juga oleh [8] dengan arduino uno yang dibuat untuk sampah organik, anorganik dan sampah metal dalam mendukung Sustainable Development Goals (SDGs). Namun dua penelitian ini belum dilengkapi dengan sistem monitoring.…”
Section: Pendahuluanunclassified
“…Despite the comprehensive implementation of mandatory household waste sorting in China, the coverage of intelligent waste management technologies is limited, and the degree of intelligence is low, with manual sorting still dominating [1]. Data from 2020 indicate that organic waste is the most common type of garbage in Yogyakarta, Indonesia, accounting for 50.21% of total waste [2]. Smart waste bins, as an innovative solution to this issue, are considered key tools in promoting sustainable urban development due to their automation and intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, research on smart waste bins has focused on their design, functional optimization, and application expansion. The application of microcontrollers like Arduino and Raspberry Pi, along with the integration of advanced technologies such as deep learning and image recognition, has significantly enhanced the functionality and practicality of smart waste bins [2,4]. Studies both in China and abroad have shown that smart waste bins have made significant progress in terms of accuracy in waste sorting, ease of operation, and environmental adaptability.…”
Section: Introductionmentioning
confidence: 99%